The Degree Of Economic Distress In Sukuk Issuing Countries - Nursilah Ahmad; Asma Abdul Rahman (Academic International Dialogue (AID) Academy, 2024)
Purpose of the study: The present study estimates the MI indicator for 19 sukuk issuing countries. The Misery Index (MI) is an economic indicator calculated by adding the unemployment rate to the inflation rate for an economy. It measures the degree of economic distress in an economy.